Effect of ALDH2 on Sleep Disturbances in Patients with Parkinson’s Disease - Lin, Chia-Yen (Sci Rep, 2019)
Monoamine neurotransmitters play essential roles in the regulation of arousal and sleep. Impaired metabolism of monoamine neurotransmitters could result in the accumulation of neurotoxic aldehyde metabolites and, hence, neuronal degeneration. Aldehyde dehydrogenases play an important role in the metabolism of the neurotoxic aldehyde metabolites, including the aldehyde metabolites of dopamine, serotonin, and noradrenaline. Deficient aldehyde dehydrogenase 2 (ALDH2) has been suggested to result in the accumulation of these biogenic aldehydes. An ALDH2 single nucleotide polymorphism (SNP), rs671 (A), results in significantly reduced ALDH2 enzyme activity. A total of 83 Parkinson’s disease (PD) patients were recruited in this study. In addition to the genotypes of rs671, the patients were assessed with the PD sleep scale-2nd version (PDSS-2) and the Epworth sleepiness scale (ESS) for symptoms of daytime and nocturnal sleep disturbances. The patients carrying rs671 (A) had more frequent dozing while lying down to rest in the afternoon (ESS item5) (F = 7.308, p = 0.008) than the rs671 (GG) patients. The patients with rs671 (A) reported a trend toward more frequent difficulty staying asleep than the patients with rs671 (GG). (F = 3.278, p = 0.074). The results indicate that patients carrying allele rs671 (A) are more likely to experience impairment in the regulation of arousal and sleep. The results also support the hypothesis that the accumulation of neurotoxic monoamine neurotransmitter aldehyde metabolites secondary to reduced ALDH2 enzyme activity may cause more severe monoaminergic neuronal loss and, hence, more severe symptoms in the regulation of wakefulness and sleep.